Evaluation of a County Extension Office's Use of Mass Media: A User Perspective - John Fett; Theresa Shinners-Gray; Kathleen Duffy; Cara Doyle (Journal of Applied Communications, 1995)
A random sample of 399 adults in a single county were phone surveyed to measure their use, preference and satisfaction with various sources of Extension information